Computational-Aided Approach for the Optimization of Microfluidic-Based Nanoparticles Manufacturing Process - Marco Bellotti; Enrica Chiesa; Bice Conti; Ida Genta; Michele Conti; Ferdinando Auricchio; Alessandro Caimi (Annals of Biomedical Engineering, 2024)
In the last few years, the microfluidic production of nanoparticles (NPs) is becoming a promising alternative to conventional industrial approaches (e.g., nanoprecipitation, salting out, and emulsification-diffusion) thanks to the production efficiency, low variability, and high controllability of the production parameters. Nevertheless, the development of new formulations and the switching of the production process toward microfluidic platforms requires expensive and time-consuming number of experiments for the tuning of the formulation to obtain NPs with specific morphological and functional characteristics. In this work, we developed a computational fluid dynamic pipeline, validated through an ad hoc experimental strategy, to reproduce the mixing between the solvent and anti-solvent (i.e., acetonitrile and TRIS–HCl, respectively). Moreover, beyond the classical variables able to describe the mixing performances of the microfluidic chip, novel variables were described in order to assess the region of the NPs formation and the changing of the amplitude of the precipitation region according to different hydraulic conditions. The numerical approach proved to be able to capture a progressive reduction of the nanoprecipitation region due to an increment of the flow rate ratio; in parallel, through the experimental production, a progressive increment of the NPs size heterogeneity was observed with the same fluid dynamic conditions. Hence, the preliminary comparison between numerical and experimental evidence proved the effectiveness of the computational strategy to optimize the NPs manufacturing process. Graphical Abstract

Optimization of FDM 3D printing process parameters to produce haemodialysis curcumin-loaded vascular grafts - Sara Basile; Essyrose Mathew; Ida Genta; Bice Conti; Rossella Dorati; Dimitrios A. Lamprou (Drug Delivery and Translational Research, 2023)
3D printing has provided a new prospective in the manufacturing of personalized medical implants, including fistulas for haemodialysis (HD). In the current study, an optimized fused modelling deposition (FDM) 3D printing method has been validated, for the first time, to obtain cylindrical shaped fistulas. Printing parameters were evaluated for the manufacturing of fistulas using blank and 0.25% curcumin-loaded filaments that were produced by hot melt extrusion (HME). Four different fistula types have been designed and characterized using a variety of physicochemical characterization methods. Each design was printed three times to demonstrate printing process accuracy considering outer and inner diameter, wall thickness, width, and length. A thermoplastic polyurethane (TPU) biocompatible elastomer was chosen, showing good mechanical properties with a high elastic modulus and maximum elongation, as well as stability at high temperatures with less than 0.8% of degradation at the range between 25 and 250 °C. Curcumin release profile has been evaluated in a saline buffer, obtaining a low release (12%) and demonstrating drug could continue release for a longer period, and for as long as grafts should remain in patient body. Possibility to produce drug-loaded grafts using one-step method as well as 3D printing process and TPU filaments containing curcumin printability has been demonstrated. Graphical abstract

A proof of concept to define the parameters affecting poly-l-lactide-co-poly-ε-caprolactone shape memory electrospun nanofibers for biomedical applications - Silvia Pisani; Ida Genta; Tiziana Modena; Rossella Dorati; Giovanna Bruni; Marco Benazzo; Bice Conti (Drug Delivery and Translational Research, 2023)
This study is a proof of concept performed to evaluate process parameters affecting shape memory effect of copolymer poly- l -lactide-co-poly-ε-caprolactone (PLA:PCL) 70:30 ratio based nanofibrous scaffolds. A design of experiment (DOE) statistical approach was used to define the interaction between independent material and process variables related to electrospun scaffold manufacturing, such as polymer solution concentration (w/v%), spinning time (min), and needle size (Gauge), and their influence on Rf% (ability of the scaffold to maintain the induced temporary shape) and Rr% (ability of the scaffold to recover its original shape) outputs. A mathematical model was obtained from DOE useful to predict scaffold Rf% and Rr% values. PLA-PCL 15% w/v, 22G needle, and 20-min spinning time were selected to confirm the data obtained from theoretical model. Subsequent morphological (SEM), chemical-physical (GPC and DSC), mechanical (uniaxial tensile tests), and biological (cell viability and adhesion) characterizations were performed. Graphical abstract

Stability Evaluation of Ivermectin-Loaded Biodegradable Microspheres - Rossella Dorati; Ida Genta; Barbara Colzani; Tiziana Modena; Giovanna Bruni; Giuseppe Tripodo; Bice Conti (AAPS PharmSciTech, 2015)

Preparation and Characterization of an Advanced Medical Device for Bone Regeneration - Rossella Dorati; Claudia Colonna; Ida Genta; Giovanna Bruni; Livia Visai; Bice Conti (AAPS PharmSciTech, 2014)

5-methyl-pyrrolidinone chitosan films as carriers for buccal administration of proteins - Claudia Colonna; Ida Genta; Paola Perugini; Franca Pavanetto; Tiziana Modena; Maurizia Valli; Corrado Muzzarelli; Bice Conti (AAPS PharmSciTech, 2006)

Long-term release of clodronate from biodegradable microspheres - Paola Perugini; Ida Genta; Bice Conti; Tiziana Modena; Franca Pavanetto (AAPS PharmSciTech, 2001)